Relationship between spine osteoarthritis, bone mineral density and bone turn over markers in post menopausal women - El Mansouri Laila; Khazzani Hamza; Abourazzak Fatima Z; Hmamouchi Ihsane; Bennani Loubna; Rostom Samira; Allali Fadoua; Ichchou Linda; Abouqal Redouane; Hajjaj-Hassouni Najia (BMC, 2010)
Abstract Background Several studies have observed an inverse relationship between osteoporosis and spinal osteoarthritis, the latter being considered as possibly delaying the development of osteoporosis. The aim of this study was to determine the association between individual radiographic features of spine degeneration, bone mineral density (BMD) and bone-turn over markers. Methods It was a cross sectional study of 277 post menopausal women. BMD of all patients was assessed at the spine and hip using dual-energy X-ray absorptiometry. Lateral spinal radiographs were evaluated for features of disc degeneration. Each vertebral level from L1/2 to L4/5 was assessed for the presence and severity of osteophytes and disc space narrowing (DSN). For Bone turn-over markers, we assessed serum osteocalcin and C-terminal cross-linking telopeptide of type I collagen (CTX). Linear regressions and partial correlation were used respectively to determine the association between each of disc degeneration features, BMD, and both CTX and osteocalcin. Results Mean age of patients was 58.7 ± 7.7 years. Eighty four patients (31.2%) were osteoporotic and 88.44% had spine osteoarthritis. At all measured sites, there was an increase in BMD with increasing severity of disc narrowing while there was no association between severity of osteophytes and BMD. After adjustment for age and BMI, there was a significant negative correlation between CTX and DSN. However, no significant correlation was found between CTX and osteophytes and between osteocalcin and both osteophytes or DSN. Conclusion In post menopausal women the severity of disc narrowing, but not osteophytes, is associated with a generalized increase in BMD and a decreased rate of bone resorption. These results are consistent with the hypothesis that osteoarthritis, through DSN, has a protective effect against bone loss, mediated by a lower rate of bone resorption. However, spine BMD is not a relevant surrogate marker for the assessment of osteoporosis in the spine in patients with osteoarthritis and debate as to the relationship between OA and OP is still open because of the contradictory data in the literature.